EFEKTIFITAS PROGRESSIVE MUSCLE RELAXATION DAN SLOW DEEP BREATHING TERHADAP PENURUNAN TEKANAN DARAH PADA PENDERITA HIPERTENSI DI WILAYAH KERJA PUSKESMAS GAMPING 2 YOGYAKARTA - Niken Setyaningrum (STIKes Surya Global Yogyakarta, 2016)
Background : Hypertension is one of the deadliest diseases in the world and is currently listed as the third killer disease after heart disease and cancer. Based on the 2014 survey sample registration hypertension is the fifth leading causes of death in Indonesia. WHO estimated in 2025 the incidence rate of hypertension increased by 29.2%. If not identified properly it can worsen the condition of patients with hypertension. Hypertension can be controlled by non-pharmacological therapy using progressive muscle relaxation techniques and slow deep breathing relaxation.Objective : The purpose of this study was to determine the effectiveness of progressive muscle relaxation and slow deep breathing techniques to decrease blood pressure in the working area of gamping 2 public health centre of YogyakartaMethods : The design of this research is Quasi-experimental Design with Comparison Group. Sampling technique was using purposive sampling. The study was conducted in Gamping 2 Yogyakarta public health center’s working area. The sample size in this study were 60 respondents to the division of each sample of 20 respondents in the intervention group, control group 1 and the control group 2. Analysis of the data in this study using kruskal-Wallis and post-hoc post-hoc Mann-Whitney.Result : The results of this research is that there is a significant difference of the decrease of systolic blood pressure between the intervention group and control group 1 and control group 2 (p=0.001), diastolic blood pressure (p=0.026) and slow deep breathing is done simultaneously be used to lower blood pressure. Keywords: Hypertension, Progressive Muscle Relaxation, Slow Deep Breathing